Analisis Pengaruh Profitabilitas, Likuiditas Dan Solvabilitas Terhadap Nilai Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Allend Tio; Argo Putra Prima (Owner : Riset dan Jurnal Akuntansi, 2022)
The aims of this research is to analyze and prove the impact of profitability as proxied by return on assets, liquidity proxied by current ratio and solvency as proxied by debt to equity ratio partially and simultaneously on firm value in mining companies that listed on IDX for the 2015-2020 period. The research was conducted with a quantitative approach, with a purposive sampling technique. The analysis technique used is multiple linear regression with partial test hypothesis testing (t test), simultaneous test (F test), and multiple determination coefficient test (R2) with the help of SPSS version 25 program. The results of the study show that 1) profitability is proven significant effect on firm value with a regression coefficient of -0.719; 2) liquidity is proven to have a significant effect on firm value with a regression coefficient of -1.160; 3) solvency has a significant effect on firm value with a regression coefficient of -1.354; and 4) profitability, liquidity and solvency proved to have a significant effect on firm value with a regression coefficient of 0.236. It is mean that profitability, liquidity, and solvency variables simultaneously and partially affect the firm value because the value of sig < 5%. This proves that in a mining company to increase the value of the company, it must pay attention to the profitability, liquidity, and solvency of the company.